The Effects of Acute Virtual Reality Exergaming on Mood and Executive Function: Exploratory Crossover Trial - Genta Ochi; Ryuta Kuwamizu; Tomomi Fujimoto; Koyuki Ikarashi; Koya Yamashiro; Daisuke Sato (JMIR Publications, 2022)
BackgroundVirtual reality (VR) exergaming is a new intervention strategy to help humans engage in physical activity to enhance mood. VR exergaming may improve both mood and executive function by acting on the prefrontal cortex, expanding the potential benefits. However, the impact of VR exergaming on executive function has not been fully investigated, and associated intervention strategies have not yet been established. ObjectiveThis study aims to investigate the effects of 10 minutes of VR exergaming on mood and executive function. MethodsA total of 12 participants played the exergame "FitXR" under 3 conditions: (1) a VR exergame condition (ie, exercise with a head-mounted display condition [VR-EX]) in which they played using a head-mounted display, (2) playing the exergame in front of a flat display (2D-EX), and (3) a resting condition in which they sat in a chair. The color-word Stroop task (CWST), which assesses executive function; the short form of the Profile of Mood States second edition (POMS2); and the short form of the Two-Dimensional Mood Scale (TDMS), which assess mood, were administered before and after the exercise or rest conditions. ResultsThe VR-EX condition increased the POMS2 vigor activity score (rest and VR-EX: t11=3.69, P=.003) as well as the TDMS arousal (rest vs 2D-EX: t11=5.34, P<.001; rest vs VR-EX: t11=5.99, P<.001; 2D-EX vs VR-EX: t11=3.02, P=.01) and vitality scores (rest vs 2D-EX: t11=3.74, P=.007; rest vs VR-EX: t11=4.84, P=.002; 2D-EX vs VR-EX: t11=3.53, P=.006), suggesting that VR exergaming enhanced mood. Conversely, there was no effect on CWST performance in either the 2D-EX or VR-EX conditions. Interestingly, the VR-EX condition showed a significant positive correlation between changes in CWST arousal and reaction time (r=0.58, P=.046). This suggests that the effect of exergaming on improving executive function may disappear under an excessively increased arousal level in VR exergaming. ConclusionsOur findings showed that 10 minutes of VR exergaming enhanced mood but did not affect executive function. This suggests that some VR content may increase cognitive demands, leading to psychological fatigue and cognitive decline as an individual approaches the limits of available attentional capacity. Future research must examine the combination of exercise and VR that enhances both brain function and mood.